Quality of life in patients with osteoarthritis of the hip - Majda, Anna; Walas, Karolina; Gawełek, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. According to one of the civilization threats — osteoarthritis is the most common joint disease in adults. Total joint replacement is a valuable treatment for severe osteoarthritis of the hip, significantly affecting improved Quality of Life of patients. Aim. The aim of this study was to evaluate the impact of hip replacement on quality of life of patients conditioned health. Matherial and methods. The study group consisted of 70 patients, who were treated at the Clinic of St. Luke in Bielsko-Biała. For the evaluation of the quality of life the standardized questionnaire — Nottingham Health Profile (NHP, Polish version Wrześniewski) was used. Results. At the final evaluation the improvement was observed in the following in subareas: energy level, pain, physical abilities and life areas affected: works in home, free time, social life, interests and hobbies. No change was observed in the in subareas: emotional reaction, social isolation, sleep and life areas affected: work, home life, sex life. Quality of life was determined by variable subjects such as sex and body weight. Women and persons of normal weight above found their quality of life after surgery arthroplasty. Conclusion. Total hip replacement improved Quality of Life in study group. Nursing Topics 2013; 21 (1): 29–37